Clinical outcomes following surgical treatment of lentigo maligna of the head and neck. Issue 5 (May 2021) - Crouch, Gareth; Sinha, Shiba; Lo, Serigne; Saw, Robyn P.M.; Lee, Kenneth K.; Stretch, Jonathan; Shannon, Kerwin; Guitera, Pascale; Scolyer, Richard A.; Thompson, John F.; Ch'ng, Sydney
Abstract: Introduction: Lentigo maligna (LM), a subtype of melanoma in-situ commonly occurring in the head and neck region, often presents a treatment challenge due to anatomical constraints, particularly on the face of mostly elderly patients. This study sought to assess the clinical outcomes of wide local excision of head and neck LM, identify predictors of recurrence and define optimal excision margins. Materials and Methods: Patients with LM treated between January 1997 and December 2012 were identified from the large institutional database of a tertiary center and their data were analyzed. Results: In 379 patients, 382 lesions were eligible for analysis. Median maximal lesion diameter was 10.5 mm. The mean surgical excision and histopathological clearance margins were 6.2 mm and 4.0 mm, respectively. Median follow-up was 32 months. The LM recurrence rate was 9.9%, and subsequent invasive melanoma developed in 2.3% of cases (mean Breslow thickness 0.7 mm). The recurrence rate was 27.2% if the histological margin was <3.0 mm (median time to recurrence 46.5 months) compared with 2.6% if the margin was ≥3.0 mm. The mean surgical margin required to achieve a histological clearance of ≥3.0 mm was 6.5 mm. Conclusions: Our data suggest that to minimize recurrence, a histological margin of ≥3.0 mm is required. To achieve this, a surgical margin of ≥6.5 mm was required. This is greater than the 5 mm margin recommended in some national guidelines. Careful long-term follow-up is required for all patients because of the risk of recurrence. Highlights: Ideal excision margins for lentigo maligna, a common precursor lesion to invasive melanoma, are unclear. This retrospective study suggests that histological margins ≥3.0 mm minimize recurrence risk. The mean surgical margin corresponding to this histological margin is ≥ 6.5 mm